Implementasi Keputusan Presiden Republik Indonesia Tentang Satuan Gugus Tugas Covid 19 PT. Tatamulia Nusantara Indah Cabang Bali - Lia Ayu Lestari; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2021)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The government is very focused on dealing with this virus. In order to eradicate the spread of this virus, the Government issued Presidential Decree No. 7 of 2020 concerning the Task Force for the Acceleration of Handling CoronaVirus Disease 2019 (Covid 19). PT Tatamulia Nusantara Indah is one of the largest contractor companies in Indonesia. This study aims to determine the implementation and understand what factors are the obstacles and efforts to overcome them in implementing the decision of the President of the Republic of Indonesia regarding the assistance of the Covid 19 task force at the Contracting Company PT Tatamulia Nusantara Indah Bali Branch. This research is empirical legal research. Where the results of this study indicate that the implementation of the Presidential Decree on the Task Force for the Acceleration of Handling Covid 19 and the obstacles faced and countermeasures in implementing the Presidential Decree at PT. Tatamulia Nusantara Indah Bali branch so that it can be carried out as expected.